A study of biblical texts in the light of cuneiform sources and archaeological discoveries (Journal of the College of Basic Education, 2022)
Since the first half of the 19thcentury onwards ، the finding of archaeological excavations have achieves a great effective role in the human knowledge by discovering several libraries and archives containing ritual ، my thological and historical texts ، relating to ancient civilization rose in the near east، and especially the civilization in Mesopotamia ، the land of the two rivers (where Iraq now) . The findings of excavations have drawn a clear picture of the historical aspect within the Hebrew bible ، the old testament . Yet ، the Biblical source has been considered secondary although it was the unique source before. Modern thinkers and scholars adopt the comparative method in their studies of religions and literature as well as other fields.Our study focused on the implications of the biblical texts has regarding various topics in parallel with similar topics given in cuneiform sources texts . We have tried to find out the extent of similarities and differences or metaphors in these texts and making a benefit from the current results of the biblical Geography so as to confirm or reject their contents and implications to show the historical reality clearly